The Relationship between the Determinants of Equity Prices in Nepal - Pandey, Churamani; Sunar, Krishna Bahadur (The Harvest, 2022)
The major objective of this study is to investigate the relationship of share price with dividend payout ratio, retention ratio, dividend per share, earning per share and return on equity. The samples have been chosen on the basis of easily availability of annual reports. The total number of observations is fifty having ten years annual financial data of five sampled banks. As per research design descriptive and Correlational research design have been employed. The statistical tools consist of mean, standard deviation as well as Correlation analyses. The dependent variable market price per share (MPS) is positively correlated with independent variables such as earning per share, dividend per share, return on equity and dividend payout ratio which implies that they move in the same direction. In other words, when one increases another also increases and vice versa. Moreover, retention ratio is negatively correlated with market price per share.